EFEKTIVITAS PENYALURAN PROGRAM BANTUAN LANGSUNG TUNAI MELALUI DANA DESA STUDI KASUS DI KECAMATAN TOLINGGULA - Didit Waluyo; Fenti Prihtini Tui; Yakob Noho Nani (Journal Education and Government Wiyata, 2025)
This study aims to determine the effectiveness of the distribution of direct cash assistance programs through Village funds, a case study in Tolinggula District by taking three villages as samples through several indicators of effectiveness measurement (1) timeliness, (2) accuracy in determining choices, (3) accuracy of targets. The research method used is qualitative with a descriptive research type. Data collection is carried out through observation, interviews, and documentation. The results of this study indicate that the distribution of direct cash assistance in Tolinggula District, especially in Limbato Village, Papualangi Village, and Cempaka Putih Village has been running effectively in accordance with the criteria for recipients of direct cash assistance as stated in the Minister of Finance's instruction Number 222 / PMK.07 / 2020. In terms of measuring the effectiveness of the distribution of direct cash assistance (1) timeliness, the distribution of direct cash assistance is in accordance with the predetermined time standards, and according to the schedule that has been set. (2) accuracy in determining choices, through this measurement the distribution of direct cash assistance to see who is included in the criteria is correct. (3) Target accuracy, according to the results of the interview, the distribution of direct cash assistance in Tolinggula District was right on target according to the Minister of Finance Regulation Number 222/PMK.07/2020.